The reactive cholera vaccination campaign in urban Dhaka in 2022: experience, lessons learned and future directions - Zahid Hasan Khan; Md Taufiqul Islam; Mohammad Ashraful Amin; Nabid Anjum Tanvir; Fahima Chowdhury; Farhana Khanam; Taufiqur Rahman Bhuiyan; Tajul Islam A Bari; Aninda Rahman; Md Nazmul Islam; Ashraful Islam Khan; Firdausi Qadri (Public Health in Practice, 2024)
Introduction: An upsurge of diarrheal cases occurred in Dhaka, Bangladesh, with approximately 30% of the cases being identified as cholera in 2022. To combat this situation, a reactive Oral Cholera Vaccination campaign was organized in five highly cholera-affected areas of Dhaka city. The paper is a descriptive tale of experience gathering, organization and implementation of reactive oral cholera vaccination campaign. Study design: This is a descriptive report of a reactive oral cholera vaccination campaign. Methods: Population density maps were generated using GIS technology before launching the campaign. The target population comprised individuals aged over one year, excluding pregnant women, totaling 2,374,976 people residing in above mentioned areas. The campaign utilized Euvichol-Plus, an OCV with adherence to the necessary cold chain requirements. Total 700 teams, each consisting of six members, were deployed across the five zones. The campaign was conducted in two rounds, where first round took place in June–July 2022, followed by second round in August 2022. During the campaign, data on adverse events following immunization (AEFI) was collected. Expert teams from various government and non-government organizations monitored regularly and ensured the campaign's success. Results: The first round achieved a coverage rate of 99%, whereas in the second round, 86.3% of individuals among the first dose recipients. During the campaigns, a total of 57 AEFIs were reported. Conclusions: This campaign serves as a model for a multispectral approach in combating cholera epidemics, highlighting the collaborative efforts of policymakers, health authorities, local communities, and health partners.